La intervención de la familia en el proceso psicoterapéutico de pacientes con dependencia a sustancias psicotrópicas de la comunidad terapéutica Posada Solidaria de la ciudad de Loja en el periodo febrero - julio. - Cabrera Sandoval, Pablo Andrés (2014)
Addiction has now become an important issue to be addressed from the contention that the legalization of drugs in our country, which is directly affecting society and families of consumers of psychotropic substances is achieved, since that families are absorbing the outcomes thereof. The drug reaches result in personal, social and above all family deterioration; it is this which remains in constant contact with the family dependent on psychotropic substances, resulting in a change in family dynamics as a malfunction of the same. The overall objective of this research was to promote family involvement in the psychotherapeutic process dependent patients psychotropic substances, in order to achieve awareness among families about the importance of their involvement in the process, once captured the attention family through a psychoeducation, the specific objectives consist was performed, the first to assess the patient's family dynamics consuming psychotropic substances with reagents such as Apgar psychological and family Functioning Tets FF -SIL, which is I apply individually to each member of the family and after obtaining the results of these psychological reagents the second objective, which was developed to implement the plan psychotherapeutic intervention to the direct involvement of families dependent patients a psychotropic substance . To conduct this research work methods used Descriptive and correlational, being a correlational quantitative study that measures the degree of relationship between these two or more variables. After obtaining the results of this research in the Therapeutic Community " Posada Solidarity " of the City of Loja , it was determined that 45 % are considered Functional Families; and 55 % show a degree of psychological Dysfunctionality obtained reagents such as family Apgar Test and Family Functioning; after obtaining the information is applied a psychotherapeutic plan, which consisted of cognitive psychotherapeutic techniques - behavioral, rational - emotive and humanistic, divided into two phases, the first phase data were collected to detect the problem in the family and second significant issues such as codependency, communication, affection and forgiveness was addressed. Keywords: Addiction, psychotropic substances, family, function, dysfunction, intervention.